Temporary Visual Hallucinations in a 31-year-old Female Patient Post Falcotentorial Meningioma Resection with No History of Psychosis: A Case Report - Sipayung, Sebastian; Janitra, Raka; Hassan, Roslan; Satyanegara (Talenta Universitas Sumatera Utara, 2024)
Introduction: Falcotentorial meningiomas are rare, comprising 1%–2% of all intracranial meningiomas, arising at the junction of the falx cerebri and tentorium. These tumors may compress the quadrigeminal plate and/or splenium, leading to peduncular hallucinosis—vivid, colorful visual hallucinations of people and animals, which can persist even after tumor removal. Case Description: A 31-year-old woman with no psychosis history presented with a bilateral visual field deficit and left extremity weakness. Brain MR imaging revealed a lobulated mass attached to the right cerebellar tentorium, posterior falx cerebri, and adjacent venous sinuses. Visual field analysis showed homonym superior quadranopsia. Following craniotomy and tumor removal, histology confirmed a mixed-type meningioma. Post-surgery, the patient experienced vivid visual hallucinations that resolved in two weeks, but bilateral visual field deficits remained. A post-op CT showed reduced structural compression around the lesion with slight narrowing of the quadrigeminal cistern. Discussion : Visual hallucinations in falcotentorial meningioma patients, often as peduncular hallucinosis, occur due to compression of the quadrigeminal plate and/or splenium and may persist post-surgery if lesions are present in the cerebral peduncles or nearby midbrain areas. Conclusion: The patient's temporary hallucinations may have resulted from post-resection tissue edema causing quadrigeminal cistern narrowing or indicate lesions in the cerebral peduncles or adjacent midbrain regions.